The disabling effects of enabling social policies on organisations' human capital development practices for women. (15th January 2022) - Reichel, Astrid; Lazarova, Mila; Apospori, Eleni; Afiouni, Fida; Andresen, Maike; Bosak, Janine; Parry, Emma; Bagdadli, Silvia; Briscoe, Jon P.; Gianecchini, Martina; Suzanne, Pamela; Taniguchi, Mami
Abstract: Paid parental leave and externally provided childcare are social policies designed to enhance parents' labour force participation. These policies influence not only men's and women's decisions regarding their labour market activity but also organisational decision makers' (ODMs) expectations about their employees' availability to work and thus, their willingness to invest in their employees' human capital. Using a sample of over 13, 000 individuals from 19 countries, we investigate the interaction between gender and social policies on human capital development practices. In line with statistical discrimination theory, which suggests that ODMs hold different expectations about female and male productivity, we find that paid parental leave and externally provided childcare are negatively associated with the provision of human capital development for women but not for men.